2015
DOI: 10.5056/jnm14142
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Gut Microbiota and Efficacy of Probiotics in Functional Constipation

Abstract: Article: Change of fecal flora and effectiveness of the short-term VSL#3 probiotic treatment in patients with functional constipation Kim SE, Choi CS, Park KS, et al Functional constipation (FC) is a common symptom-based gastrointestinal (GI) disorder without organic abnormality, the prevalence of which is between 5% and 20% of the general population.1,2 The symptoms of constipation can be severe; thus, this disorder has a significant impact on patient's quality of life. 3The cause of FC remains unclear, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 40 publications
(46 reference statements)
2
34
0
2
Order By: Relevance
“…Gln supplementation may ameliorate constipation by increasing the energy harvesting capacity by Firmicutes species [48]. Additionally, obese pigs had a higher abundance of Spirochaetes than lean pigs [49], and Bifidobacterium and Bacteroides species were significantly less abundant in feces from patients with functional constipation, as compared with healthy controls [8], which is in agreement with results of the present study. Human adult and infant distal gut microbiomes had significantly higher abundance of Actinobacteria than did the swine microbiome [50].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Gln supplementation may ameliorate constipation by increasing the energy harvesting capacity by Firmicutes species [48]. Additionally, obese pigs had a higher abundance of Spirochaetes than lean pigs [49], and Bifidobacterium and Bacteroides species were significantly less abundant in feces from patients with functional constipation, as compared with healthy controls [8], which is in agreement with results of the present study. Human adult and infant distal gut microbiomes had significantly higher abundance of Actinobacteria than did the swine microbiome [50].…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, drug use should be avoided during gestation for any reason and not used as a last resort. Thus, alteration to the gut microbiota has been suggested a possible solution to constipation [8], as diet and nutritional status influence the composition and function of gut microbiota and are, therefore, considered potential therapeutic methods to alleviate constipation.…”
Section: Introductionmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T 4 probiotics have restored the gut microbiota, thus improving the symptoms of constipation [13]. A meta-analysis of probiotic consumption has shown its ability to restore the gut biota and correct dysbiosis [14].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A high tolerance to acid and bile salt means that the lactic acid bacteria can easily pass the stomach and are colonized in the intestinal tract (Bustos et al, 2012). Some studies have reported that probiotics may act as an enhancer to prevent or cure constipation in humans and animals (Indrio et al, 2014;Choi and Chang, 2015;Kim et al, 2015;Tabbers and Benninga, 2015). The live probiotics increased the colonic levels of short-chain fatty acids, which showed a laxative effect by affecting the enteral mucosa (Hu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%